Intraventricular Neurocysticercosis: A Case Report - Bahtiar, Ruzbih; Wijanarko, Ferry (Indonesian Journal of Medicine, 2018)
Background: Neurocysticercosis is the most common parasitic disease of nervous system in humans and the single most common cause of acquired epileptic seizures in the developing country. But in Indonesia, it was rarely reported. It has wide variety of clinical manifestation due to its pleomorphic nature.Subjects and Method: We reported a case of a 12 years old male with seizure and hydrocephalus due to intraventricular neurocysticercosis. A ventriculoperitoneal shunt (V-P shunt) performed to reduce the intracranial pressure due to hydrocephalus and followed by endoscopic surgery to taking sample of the neurocysticercosis and reducing the mass.Results: Pathological anatomy examination of excised mass found worm eggs. The patient received medications of albendazole and metil prednisolon.Conclusion: Intraventricular neurocysticercosis causing hydrocephalus is the commonest surgical indication, with V-P shunt placement followed by endoscopic surgery as the procedure of choice as it minimally invasive.Keyword: Intraventricular neurocysticercosis, hydrocephalus, headache, V-P shunt, endoscopic surgery.Correspondence:Ruzbih Bahtiar. General Surgery Resident, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java.Indonesian Journal of Medicine (2018), 3(1): 56-64https://doi.org/10.26911/theijmed.2018.03.01.08